COVID-19 as a trigger for racially motivated and extremist violent crime: a temporal analysis of hate crimes in Slovakia amidst a global pandemic - Piatkowska, Sylwia J. (Crime, law and social change, 2024)
The current study offers a first attempt to examine a relationship between the outbreak of the COVID-19 pandemic and racially motivated and extremist violent crime rates across regions in Slovakia. The Slovak Republic provides an interesting setting for bias crime evaluation, as the nation’s interrelation between migration, race, socioeconomic status, and social identity offers important potential drivers of bias-motivated violence. We go beyond previous work by investigating connections between the outbreak of the COVID-19 pandemic, immigration rates, employment rates, and violent hate crime incidence and victimization rates using temporal data on racially motivated and extremist violent crimes from the Ministry of the Interior of the Slovak Republic, which are linked with data on indicators of socioeconomic development from the Statistical Office of the Slovak Republic. The results illustrate the important role of a signal event such as the COVID-19 pandemic in triggering amplified threat perceptions, insofar as the COVID-19 pandemic is associated with increased violent hate crime rates, particularly in regions with higher immigration rates and low male employment rates.